Harga Diri dan Kecemasan Memilih Pasangan Hidup Wanita Dewasa Awal Fase Quarter Life Crisis - Rizky Safitri; Arini Mifti Jayanti (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2023)
Self-esteem can affect many things in life, one of which is choosing a life partner. This study aims to determine the relationship between self-esteem and anxiety choosing a life partner in early adult women who experiences a quarter life crisis. The research method used is quantitative correlation by using the Rosenberg Self Esteem Scale which has been adapted into Indonesian by Azwar (2019) and the scale for choosing a life partner based on aspects of anxiety according to Nevid (2018). The number of respondents is 110 women of early adulthood. The data analysis technique used is the Product Moment analysis technique from Karl Pearson. The results showed that there was a negative relationship between self-esteem and anxiety about choosing a life partner in adult women who experienced a quarter life crisis with r = -0.245 and p = 0.01. Minimize anxiety by increasing self-esteem by developing good relationship with others.